A systematic review of the psychological factors associated with returning to sport following injury. Issue 17 (13th October 2012) - Ardern, Clare L; Taylor, Nicholas F; Feller, Julian A; Webster, Kate E
Abstract : Background: Psychological factors have been shown to be associated with the recovery and rehabilitation period following sports injury, but less is known about the psychological response associated with returning to sport after injury. The aim of this review was to identify psychological factors associated with returning to sport following sports injury evaluated with the self-determination theory framework. Study design: Systematic review. Method: Electronic databases were searched from the earliest possible entry to March 2012. Quantitative studies were reviewed that included athletes who had sustained an athletic injury, reported the return to sport rate and measured at least one psychological variable. The risk of bias in each study was appraised with a quality checklist. Results: Eleven studies that evaluated 983 athletes and 15 psychological factors were included for review. The three central elements of self-determination theory—autonomy, competence and relatedness were found to be related to returning to sport following injury. Positive psychological responses including motivation, confidence and low fear were associated with a greater likelihood of returning to the preinjury level of participation and returning to sport more quickly. Fear was a prominent emotional response at the time of returning to sport despite the fact that overall emotions became more positive as recovery and rehabilitation progressed. Conclusions: There is preliminary evidence that positive psychological responses are associated with a higher rate of returning to sport following athletic injury, and should be taken into account by clinicians during rehabilitation.